Identification of FDA‐approved drugs that target hepatitis B virus transcription. Issue 3 (12th October 2015) - van de Klundert, M. A. A.; Zaaijer, H. L.; Kootstra, N. A.
Summary: In the treatment of chronic hepatitis B virus (HBV) infection, polymerase inhibitors successfully suppress HBV DNA production. However, the production of viral proteins continues unhindered, which hampers viral clearance. Here, we screen for compounds that suppress HBV transcription, which would prevent viral protein production. A total of 640 FDA‐approved drugs were evaluated for their ability to inhibit HBV transcription in a transfection‐based HBV reporter assay. The assay was performed in the presence and absence of the HBV accessory protein X (HBx), which is essential for in vivo HBV RNA transcription. We observed that in the absence of HBx 47, and in the presence of HBx 24 compounds suppressed transcription by more than 20%. We selected the 24 most potent compounds in each condition for further analysis. On average, the selected compounds reduced transcription by 33.9% (range: 24.1–65.8%) in the absence of HBx expression, and 30.6% (range: 20.4–48.9%) in the presence of HBx. The two selections of 24 compounds had 12 compounds in common, resulting in a final selection of 36 compounds, which were evaluated for their capacity to suppress HBV replication in constitutively HBV‐replicating HepG2.2.15 cells. Twenty‐three of these compounds reduced HBV replication by interfering with RNA transcription. Further analysis revealed that one of the compounds, terbinafine, potently and specifically suppressed HBx‐mediated HBV RNA transcription in HepG2 cells. Inhibition of HBV protein production is a promising step towards HBV clearance. In combination with an HBV polymerase inhibitor, the added suppression of HBV RNA transcription may markedly improve antiviral treatment outcome.